Cervicofacial Cellulitis due to Staphylococcus aureus with Jugular Vein Thrombosis and Multiple Septic Pulmonary Embolism: A Lemierre-Like Syndrome - Ibrahima Niang; Latyr Junior Diouf; Papa Abdou Diop; Daouda Thioub; Alassane Sarr; Khadidiatou Ndiaye Diouf; Geraud Lera Akpo; Abdoulaye Dione Diop; Sokhna Ba (Case Reports in Infectious Diseases)
This is the case of a 28-year-old male patient with no particular pathological history who presented with an inflammatory swelling of the right cheek with pus in an infectious context. Cervicofacial CT with contrast injection allowed the diagnosis of a right cervicofacial cellulitis, associated with a jugular venous thrombosis extending to the superior vena cava. It also revealed septic pulmonary metastases in the form of multiple excavated pulmonary nodules. The analysis of the pus sample allowed the isolation of Staphylococcus aureus as the causative germ. This led to the diagnosis of a Lemierre-like syndrome, which is a variant of the Lemierre syndrome. Despite appropriate antibiotic treatment and anticoagulation, the patient died after 16 days of hospitalization.